2010 Pittsburgh, Pennsylvania, June 20 - June 23, 2010 2010
DOI: 10.13031/2013.29692
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Production from Waste Potato Mash By Using Saccharomyces cerevisiae

Abstract: Bio-ethanol is one of the energy sources that can be produced by renewable sources. Waste potato mash was chosen as a renewable carbon source for ethanol fermentation because it is relatively inexpensive compared with other feedstock considered as food sources. However, a pretreatment process is needed: specifically, liquefaction and saccharification processes are needed to convert starch of potato into fermentable sugars before ethanol fermentation. In this study, hydrolysis of waste potato mash and growth pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 12 publications
3
15
0
Order By: Relevance
“…The analyzer is consisted of a specific ethanol membrane, system buffer, and standard ethanol solution (2 g/L). The samples that contained ethanol higher than 2 g/L, were diluted with deionized water …”
Section: Ethanolsupporting
confidence: 93%
“…The analyzer is consisted of a specific ethanol membrane, system buffer, and standard ethanol solution (2 g/L). The samples that contained ethanol higher than 2 g/L, were diluted with deionized water …”
Section: Ethanolsupporting
confidence: 93%
“…at different inoculum size, pH-value 5 and initial sugar con (90 g/l) Ethanol yield decrease with increased inoculum size due to increase biomass which required more substrates in media with time sugar concentration decreased. The results in this study similar to other study [19] sugar conversion was continuing simultaneously during the fermentation, and after 52h of fermentation, sugar was completely consumed in both cases as shown in Fig. 8…”
Section: Effect Of Inoculum Size On Bioethanol Productionsupporting
confidence: 90%
“…Neelakandan and Usharan (2009) studied different inoculum size (2, 4, 6, 8 and 10% v/v) for a period of 24 h and observed that the maximum ethanol concentration that is, 8.8% was obtained at 10% inoculum size. In comparison of these results, Izmirlioglu and Demirci (2012) showed that 3% inoculum size was optimum for maximum ethanol concentration and production rate. Turhan et al (2010) reported the ethanol production from carob extract by using S. cerevisiae and found that maximum ethanol concentration; ethanol productivity and ethanol yield were 42.90 g/L, 3.7 g/L/h and 45.0%, respectively, obtained with an initial inoculum of 3%.…”
Section: Optimization Of Inoculum Size For Ethanol Productionmentioning
confidence: 97%